2016
DOI: 10.18632/oncotarget.10670
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with an SLC12A1 antagonist inhibits tumorigenesis in a subset of hepatocellular carcinomas

Abstract: A central aim in cancer research is to identify genes with altered expression patterns in tumor specimens and their potential role in tumorigenesis. Most types of tumors, including hepatocellular carcinoma (HCC), are heterogeneous in terms of genotype and phenotype. Thus, traditional analytical methods like the t-test fail to identify all oncogenes from expression profiles. In this study, we performed a meta-Cancer Outlier Profile Analysis (meta-COPA) across six microarray datasets for HCC from the GEO databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…The expression of α-SMA and Col4a3 mRNA was higher in the tumorous than non-tumorous tissues of all mice, regardless of chemerin-156 overexpression (Figure 4a,b). Consistent with previous reports [32][33][34][35], early growth response gene-1 (Egr-1), solute carrier family 12 member 1 (Slc12a1), and serine peptidase inhibitor, Kazal type 1 (Spink1) mRNA levels were higher in tumorous than non-tumorous tissues, whereas glucose-6-phosphatase (G6PC) was reduced (Figure 4c-f). However, this effect was similar regardless of chemerin-156 overexpression.…”
Section: Genes and Proteins Already Described To Be Differentially Exsupporting
confidence: 92%
“…The expression of α-SMA and Col4a3 mRNA was higher in the tumorous than non-tumorous tissues of all mice, regardless of chemerin-156 overexpression (Figure 4a,b). Consistent with previous reports [32][33][34][35], early growth response gene-1 (Egr-1), solute carrier family 12 member 1 (Slc12a1), and serine peptidase inhibitor, Kazal type 1 (Spink1) mRNA levels were higher in tumorous than non-tumorous tissues, whereas glucose-6-phosphatase (G6PC) was reduced (Figure 4c-f). However, this effect was similar regardless of chemerin-156 overexpression.…”
Section: Genes and Proteins Already Described To Be Differentially Exsupporting
confidence: 92%
“…A previous study showed that bumetanide, a SLC12A1 antagonist, inhibited cell proliferation, tumorigenesis, and metastasis in HCC cell lines (59). The study also suggested that bumetanide slows down tumor growth by interfering with the cell cycle rather than by inducing cytotoxicity (59). Studies testing the ability of bumetanide to enhance tumor necrosis in a rat model of N1-S1 HCC.…”
Section: Discussionmentioning
confidence: 98%
“…Reports about the specific function of SLC12A8 on cancer cells or normal cells proliferation and EMT were limited. Via reviewing the published articles, we observed that SLC12A1, a member of SLC12A family, was a positive regulator of WNK/ERK5 pathway, which can promote cell proliferation and survival [ 11 ]. Moreover, suppressing SLC12A1 might inhibit proliferation-related genes like Cyclin D1, a key proliferation checkpoint [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The family has two major branches: one is a sodium-dependent cotransporter, including SLC12A2, SLC12A1, and SLC12A3, and the second is a potassium and chloride cotransporter containing four members (SLC12A4, SLC12A5, SLC12A6, and SLC12A7); besides, there are also two other members, SLC12A8 and SLC12A9, whose functions have not been revealed [ 8 , 9 ]. From the current researches on SLC12 family, we learned that the expression of SLC12A1 is associated with glioma and hepatocellular carcinomas [ 10 , 11 ]. Moreover, it has been reported that the overexpression of SLC12A5 promoted the development and metastasis of tumor and is highly related to the significant decrease in patients’ survival with colorectal carcinoma and ovarian carcinoma [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%